THE PREPARATION OF POLYCAPROLACTONE FIBERS FILM CONTAINING ARTOCARPUS LAKOOCHA EXTRACT BY ELECTROSPINNING TECHNIQUE FOR ANTIBACTERIAL ACTIVITIES - Chutima, Ruangwut; Sutjarittangtham, Krit (PSRU Journal of Science and Technology, 2021)
This research, the polycaprolactone fibers containing A. lakoocha extract were prepared by electrospinning technique. The optimum condition for fibers formation was investigated and tested for the antibacterial activity. The results showed that the optimum condition of polycaprolactone fibers was 16 w/v% of polycaprolactone solution. The electrospinning conditions were as follows; the diameter of metallic needle was 0.8 mm, the distance between the needle tips to the collector was 20 cm and the electric field was 90 kV/m. The results of the A. lakoocha extraction were found that, the %yield of 5.3 by weight. Minimum Inhibitory Concentration (MIC) of A. lakoocha crude extract was in the range of 3.12–6.25 mg/ml. After preparation of polycaprolactone fibers with the A. lakoocha extract, the viscosity of the polymer solution was increased with increasing the concentration of the A. lakoocha extract. For the antibacterial tests by disc diffusion method, the polycaprolactone ﬁber with the A. lakoocha extract were tested against Bacillus subtilis (B. subtilis), Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli). The antibacterial activity of polycaprolactone ﬁber with the A. lakoocha extract at 8.0 w/V% indicated that the inhibition zone was 12.0±0.05 mm and 9.2±0.10 mm against B. subtilis and S. aureus, and the inhibition zone was not found after testing with E. coli. Respectively. From the properties of the polycaprolactone fiber film prepared by the electrospinning technique and the antibacterial properties of the A. lakoocha extract, the fibrous film could be developed to use as a wound dressing for prevent infection in wound.